MACROECONOMIC ANALYSIS OF THE CONSTRUCTION SECTOR IN PERU - Palomino Silva, Julio (2017)
This article tries to analyze the main characteristics, strengths, opportunities and risks of the construction sector. This will review the internal and external factors that influence the decisions and results of companies included in this area. Regarding the general environment, a generic perspective of the data surrounding the industry will be reviewed, presenting the macroeconomic figures of the environment and the evolution of the sector. To obtain the results, a review of the main reports issued by specialized public and private institutions was carried out, as well as information from the main statistical series of the Central Reserve Bank of Peru. Among the main results, it was determined that construction has been positioned in recent years as a sector to boost the country’s economic growth and this will continue for at least the next three years due to the expansion of public investment and construction projects (Shopping malls, department stores, homes, hydroelectric and thermoelectric power plants, irrigation projects, expansion and modernization of industrial plants and mining centers, construction of roads and airports, among others). The article ends with a SWOT analysis of the sector.